The Dynamics of Conflict Resolution and the Potential for Disintegration in West Papua in the Context of the Unity of the Republic of Indonesia: An Analysis of Conflict and Disintegration in the Papua Region - Fauzi Ismail (Doctoral Program of Social Science Pasundan University, 2023)
This research is the result of a summary and analysis of social media, interviews, and public discussions on conflict resolution and the issue of Papua's separation from the unitary state of the Republic of Indonesia. The study employs a method that includes social media description, such as Google and YouTube, interviews with the Papuan community in Bandung, and an analysis of public discussions related to the issue of West Papua. The results of this research include a discussion of the root causes of the conflicts in the Papua region, which have claimed many victims from both the Indonesian National Army (TNI), the Indonesian National Police (POLRI), and other civilians. The government has made several offers, such as Special Autonomy (Otsus), providing significant budget allocations from the national budget for Papua, road construction, housing, market relocations, and more. However, up to this point, there hasn't been a clear solution to the issues. This research fills a gap in the understanding of the Papua conflict, which often focuses on issues of violence, human rights violations, and so on. For example, the thesis titled